Developing a prognostic model for localized Ewing sarcoma family of tumors: A single institutional experience of 224 cases treated with uniform chemotherapy protocol. Issue 6 (29th December 2014) - Biswas, Bivas; Rastogi, S.; Khan, S.A.; Shukla, N.K.; Deo, S.V.S.; Agarwala, S.; Mohanti, B.K.; Sharma, M.C.; Vishnubhatla, Sreenivas; Bakhshi, S.
Abstract : Background: Data on patients with localized Ewing sarcoma family of tumors (ESFT) who have received a uniform chemotherapy protocol are minimal. Methods: This is a single institutional review of patients with ESFT treated between June 2003 and November 2011. Results: 224/374 (60%) patients with ESFT presented with localized disease; median age was 15 years (range: 0.1–55). Ninety‐nine patients underwent surgery of which 50 received adjuvant radiotherapy; 80 patients received radical radiotherapy following neoadjuvant chemotherapy. At median follow‐up of 40.2 months (range: 1.3–129), 5‐year EFS, OS, and local‐control‐rate, were 36.8 ± 3.6%, 52.4 ± 4.3%, and 63 ± 4.3%, respectively. In multivariate analysis, tumor diameter >8 cm ( P = 0.03), symptom duration >4 months ( P = 0.04), and WBC >11 × 10 9 /L ( P = 0.003) predicted inferior EFS; spine/abdomino‐pelvic primary ( P = 0.009) and WBC >11 × 10 9 /L ( P = 0.003) predicted inferior OS. Tumor size >8 cm ( P = 0.03) and radical radiotherapy as local treatment ( P = 0.01) predicted inferior local‐control‐rate. Conclusion: Prognostic hazard models for EFS and OS based on significant prognostic factors suggested that patients with combination of ESFT of spine/abdomino‐pelvic region and baseline WBC >11 × 10 9 /L had inferior OS (hazard ratio 4.44, P < 0.001) while patients with combination of ESFT with symptom duration >4 months, tumor diameter >8 m and baseline WBC >11 × 10 9 /L had inferior EFS (hazard ratio 3.89, P = 0.002). J. Surg. Oncol. 2015 111:683–689 . © 2014 Wiley Periodicals, Inc.